Investigating the Relationship Between Insulin Treatment Refusal and Psychosocial Factors in Type 2 Diabetic Patients - Sahin, Veysel; Yakar, Burkay; Gomleksiz, Mehtap; Onalan, Erhan; Kilinc, Faruk (Pera Yayincilik Hizmetleri, 2024)
Objective: Refusal of insulin therapy is an important barrier in the treatment of type 2 diabetes mellitus (T2DM). The current study aimed to investigate the effect of psychosocial status of diabetic patients on insulin treatment acceptance and refusal. Methods: This cross-sectional study was conducted with age and gender matched 80 diabetic patients who accepted insulin therapy and 80 diabetic patients who refused insulin therapy. Participants were interviewed face-to-face using a questionnaire consisting of five sections: socio-demographic, depression, anxiety, fear of self-injection and adherence to diabetes treatment. Results: There was no significant difference between the two groups in terms of age and gender. The beck depression scale score (p=0.002) and beck anxiety scale score (p<0.001) of the participants who refused insulin treatment were statistically significantly higher than the group who accepted the treatment. The injection fear scale score of the group who refused insulin treatment was statistically significantly higher than those who accepted insulin treatment (p<0.001). There was a significant negative correlation between injection fear score and treatment adherence scale score in both participants who accepted (r:-0.224; p:0.045) and refused insulin treatment (r:-0.309; p:0.005). Conclusion: The current study showed that depressive and anxiety moods of the individuals caused insulin therapy refusal. In addition, fear of injection was another factor causing insulin treatment refusal. Depression and fear of injection were also found to negatively affect adherence to treatment.
Keywords: Diabetes mellitus; insulin; medication adherence; treatment refusal